Prevalence and factors associated with latent tuberculosis infection in an indigenous population in the Brazilian Amazon - Jocieli Malacarne; Diana Patricia Giraldo Rios; Cosme Marcelo Furtado Passos da Silva; José Ueleres Braga; Luiz Antonio Bastos Camacho; Paulo Cesar Basta (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract: INTRODUCTION Recent studies have shown a high incidence and prevalence of latent tuberculosis infection (LTBI) in indigenous populations around the World. We aimed to estimate the prevalence and annual risk of infection (ARI) as well as to identify factors associated with LTBI in an indigenous population from the Brazilian Amazon. METHODS We conducted a cross-sectional study in 2011. We performed tuberculin skin tests (TSTs), smears and cultures of sputum samples, and chest radiographs for individuals who reported cough for two or more weeks. Associations between LTBI (TST ≥5mm) and socio-demographic, clinical, and epidemiological characteristics were investigated using Poisson regression with robust variance. Prevalence ratio (PR) was used as the measure of association. RESULTS We examined 263 individuals. The prevalence of LTBI was 40.3%, and the ARI was 2.4%. Age ≥15 years [PR=5.5; 95% confidence interval (CI): 3.5-8.6], contact with tuberculosis (TB) patients (PR=3.8; 95% CI: 1.2-11.9), previous TB history (PR=1.4; 95% CI: 1.2-1.7), and presence of Bacillus Calmette-Guérin (BCG) scar (PR=1.9, 95% CI: 1.2-2.9) were associated with LTBI. CONCLUSIONS Although some adults may have been infected years prior, the high prevalence of infection and its strong association with age ≥15 years, history of TB, and recent contact with TB patients suggest that the TB transmission risk is high in the study area.